2023
DOI: 10.1155/2023/3401001
|View full text |Cite
|
Sign up to set email alerts
|

Application of NAD+-Dependent Electrochemical Dehydrogenase Biosensors in Human Physiological Fluids: Opportunities and Challenges

Abstract: Electrochemical enzymatic biosensors represent a promising, low-cost technology for point-of-care (POC) diagnostics that allows fast response and simple sample processing procedures. In this review, we summarize up-to-date literature on NAD+/NADH (β-nicotinamide adenine dinucleotide)-dependent electrochemical dehydrogenase biosensors and highlight their applications in human physiological fluids. A brief comparison of various enzyme immobilization procedures is first presented, discussing preparation processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…These methods are usually based on tunable localized surface plasmon resonance (LSPR) and colloidal stability in the absence or presence of an analyte resulting in different colours [34]. Extensive research has been published on electrochemical NAD(P)/NAD(P)H biosensors functionalized with varying materials of nanocomposite and oxidoreductase enzymes [35][36][37][38][39][40]. To the best of our knowledge, limited research outputs have been reported for the colorimetric detection of NAD(P)/NAD(P)H using plasmonic gold nanoparticles immobilized with hydrogenase or reductase enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are usually based on tunable localized surface plasmon resonance (LSPR) and colloidal stability in the absence or presence of an analyte resulting in different colours [34]. Extensive research has been published on electrochemical NAD(P)/NAD(P)H biosensors functionalized with varying materials of nanocomposite and oxidoreductase enzymes [35][36][37][38][39][40]. To the best of our knowledge, limited research outputs have been reported for the colorimetric detection of NAD(P)/NAD(P)H using plasmonic gold nanoparticles immobilized with hydrogenase or reductase enzymes.…”
Section: Introductionmentioning
confidence: 99%